PR Management Theory in the Light of Philosophy - Suprayitno, Hery; Jamaluddin, Jamaluddin (Formosa Journal of Applied Sciences, 2025)
This research examines public relations management theory through a philosophical perspective with a focus on the integration of ethical values, epistemology and ontology. This approach aims to enrich the understanding of the importance of sustainability, justice, and authentic relationships in strategic communication between organizations and the public. The two-way symmetrical model, Foucault's epistemology of power, and Martin Buber's concept of relations are the theoretical foundations explored in this analysis. The study utilizes a literature review method with a hermeneutic approach to identify the relevance of the philosophical values to modern PR practice. Results show that the incorporation of these values can improve communication effectiveness, create sustainable relationships, and promote inclusiveness and social responsibility.